SAT0133 Predictors of pain and its change over time in fibromyalgia. (1st June 2001) - Dessein, PH; Stanwix, AE; Moomal, Z
Abstract : Background: Widespread pain is the central feature of fibromyalgia (FM). The role of physical as opposed to psychological mechanisms in FM pain remains a matter of controversy. Objectives: In the present study, we evaluated the dependency of FM pain on other FM clinical features as assessed by the Fibromyalgia Impact Questionnaire (FIQ). Methods: Forty two consecutive patients, who had been followed up for at least 2 months, were enrolled. Their mean (SD, range) age, disease duration and follow up duration were 42 (12, 15–78), 8 (11, 0.3–45) and 2.9 (2.2, 0.28 -8.6) years, respectively. They completed FIQ scores as applied to their health status at enrolment in the clinic and at the time of the study. Statistical analyses were done by simple linear regression analyses and one-way analysis of variance. Results were expressed as mean (SD) and a p < 0.05 was considered significant. Results: The pain visual analogue scale was 8.9 (1.3) at enrolment versus 2.4 (1.9) at the time of the study (p < 0.001). At enrolment, pain was predicted by morning tiredness (p < 0.001), FM symptom interference with work (p < 0.001) and stiffness (p = 0.001). At the time of the study, pain was predicted by tiredness (p < 0.001), morning tiredness (p < 0.001), FM symptom interference with work (p = 0.003) and stiffness (p = 0.03). Improvement in pain was predicted by pain at enrolment (p = 0.007) (and by no other baseline FIQ scores) and improvements in tiredness (p < 0.001), morning tiredness (p < 0.001), FM symptom interference with work (p < 0.001) and stiffness (p = 0.002). Conclusion: Pain and fatigue were strongly interrelated in our FM patients. The physical symptoms fatigue, stiffness and FM symptom interference with work consistently predicted FM pain and its change over time. In contrast, the psychological variables anxiety and depression, as assessed by the FIQ, did not relate to FM pain. References: Goldenberg DL. Arch Intern Med. 1999;159 :777–85 Dessein PH, et al . Pain Rev. 1997;4:79–88 Burckhardt CS, et al . J Rheumatol. 1991;18:728–37